Pengaruh Simulasi Permainan Boardgame: Find the Notice Edusex Terhadap Daya Tarik dan Sikap Remaja Tentang Free Sex - Oktavia, Jinhan Nur; Arwani, Arwani; Pertiwi, Estuasih Dyah; Widyawati, Melyana Nurul (MEDIA KESEHATAN MASYARAKAT INDONESIA, 2024)
Latar belakang: Aktivitas seks tanpa perlindungan dapat berisiko menyebabkan HIV/AIDS dan Infeksi Menular Seksual (IMS), sangat mengkhawatirkan, terutama di kalangan remaja sampai dengan rentang usia produktif usia 15-30 tahun seperti terlihat dari 573 kasus HIV/AIDS dan 802 kasus IMS di Kota Malang. Meskipun upaya oleh Kementerian Kesehatan telah dilakukan, angka IMS dan HIV/AIDS tetap tinggi. Penelitian ini bertujuan untuk menganalisis pengaruh pemberian simulasi permainan BoardGame: Find the Notice Edusex terhadap daya tarik dan sikap remaja tentang seksual bebas.Metode: Penelitian ini menggunakan desain Quasi-Experimental dengan Non-Equivalent Pre-Test Post-Test with Control Group Design. Sampel dipilih melalui proportional random sampling berjumlah 34 responden untuk masing-masing kelompok intervensi dan kelompok kontrol. Analisis data yang digunakan pada penelitian ini adalah uji homogenitas Saphiro Wilk, paired t-test dan independent t-test. Penelitian ini menggunakan variabel independen yaitu Simulasi Permainan BoardGame: Find the Notice Edusex, dan variabel dependen yaitu Daya tarik dan sikap remaja tentang Free Sex. Instrumen yang digunakan pada penelitian ini adalah permainan BoardGame: Find the Notice Edusex, kuesioner daya tarik, kuesioner sikap, leaflet edukasi seksual.Hasil: Penelitian ditemukan bahwa Boardgame: Find the Notice Edusex sudah sesuai berdasarkan uji ahli sebanyak 91%. Terdapat pengaruh pemberian simulasi permainan BoardGame: Find the Notice Edusex terhadap daya tarik remaja dibandingkan dengan pemberian edukasi leaflet edusex (p=0,048) dan sikap remaja tentang free sex (p = 0,007).Simpulan: BoardGame: Find the Notice Edusex efektif digunakan sebagai media edukasi seksual terhadap daya tarik dan sikap remaja tentang free sex.Kata kunci: Boardgame; Daya Tarik; Sikap; HIV/AIDS; IMS ABSTRACTTitle: The Influence of Boardgame: Find the Notice Edusex on Attractiveness and Adolescent Attitudes About Free SexBackground: Sexual activity without protection can risk causing HIV/AIDS and Sexually Transmitted Infections (STIs), which is very worrying, especially among teenagers up to the productive age range aged 15-30 years as seen from 573 cases of HIV/AIDS and 802 cases of STIs in Malang City . Despite efforts by the Ministry of Health, STI and HIV/AIDS rates remain high. This research aims to analyze the effect of providing the simulation game BoardGame: Find the Notice Edusex on the attractiveness and attitudes of teenagers regarding sexual promiscuity.Method: This research uses a Quasi-Experimental design with Non-Equivalent Pre-Test Post-Test with Control Group Design. The sample was selected through proportional random sampling totaling 34 respondents for each intervention group and control group. Data analysis used in this research was the Shapiro Wilk homogeneity test, paired t-test and independent t-test. This research uses an independent variable, namely the Board Game Simulation Game: Find the Notice Edusex, and the dependent variable is the attractiveness and attitude of teenagers regarding Free Sex. The instruments used in this research were the Board Game: Find the Notice Edusex, attractiveness questionnaire, attitude questionnaire, sexual education leaflet.Result: Research found that Boardgame: Find the Notice Edusex was 91% appropriate based on expert testing. There was an effect of providing the simulation game BoardGame: Find the Notice Edusex on the attractiveness of teenagers compared to providing educational leaflets Edusex (p=0.048) and teenagers' attitudes about free sex (p = 0.007).Conclusion: BoardGame: Find the Notice Edusex is effectively used as a medium for sexual education regarding the attractiveness and attitudes of teenagers regarding free sex.Keywords: Boardgame: Attraction; Attitude; HIV/AIDS; STIs